Electric vehicle charging using roof top photovoltaic controlled with new hybrid optimization technique - Dhamodharan Selvaraj; Dhanalakshmi Rangasamy (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
In this decade, electric car technology has advanced at a breakneck pace. People are also using electric vehicles more since they are more inexpensive. Electric car charging is one of the issues that most sectors confront, as there are many cities in India where charging stations have yet to be established. In this paper, an innovative approach for charging a vehicle while on the move is presented, utilising the solar panels on the vehicle's roof. The panels collect energy from the sun and use it to charge the vehicle's battery. Even when the vehicle is driving down the road, this happens. Partial shading is a concern for solar panels when travelling on the road. In this paper, a new hybrid optimization technique combining grey wolf optimization and crow search algorithms (GWO-CSA) is employed to compare an electric car model to the traditional particle swarm optimization (PSO) approach. The MATLAB simulation results demonstrate the vehicle's performance and tracking efficiency.